2015
DOI: 10.3923/jms.2015.147.154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Toxoplasma gondii Antibodies among Pregnant Women Attending Maiduguri Teaching Hospital, Nigeria

Abstract: is an International, peer-reviewed scientific journal that publishes original article in experimental & clinical medicine and related disciplines such as molecular biology, biochemistry, genetics, biophysics, bio-and medical technology. JMS is issued eight times per year on paper and in electronic format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 30 publications
6
21
5
1
Order By: Relevance
“…This result is comparable to a study in Maiduguri, Borno state, which reported 52.7% of the sampled pregnant women to be susceptible to T. gondii infection. 23 The results from this study are comparable to studies in Lagos and Maiduguri that reported 7.6 and 8.9% for anti-T. gondii IgM, and 32.6 and 40.0% for IgG antibodies, respectively. 21,23 However, our study results are unlike those conducted in Zaria, Sokoto and Osogbo which reported seropositivity of anti-T. gondii IgG as 29.1, 27.7 and 30.4%, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This result is comparable to a study in Maiduguri, Borno state, which reported 52.7% of the sampled pregnant women to be susceptible to T. gondii infection. 23 The results from this study are comparable to studies in Lagos and Maiduguri that reported 7.6 and 8.9% for anti-T. gondii IgM, and 32.6 and 40.0% for IgG antibodies, respectively. 21,23 However, our study results are unlike those conducted in Zaria, Sokoto and Osogbo which reported seropositivity of anti-T. gondii IgG as 29.1, 27.7 and 30.4%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…23 The results from this study are comparable to studies in Lagos and Maiduguri that reported 7.6 and 8.9% for anti-T. gondii IgM, and 32.6 and 40.0% for IgG antibodies, respectively. 21,23 However, our study results are unlike those conducted in Zaria, Sokoto and Osogbo which reported seropositivity of anti-T. gondii IgG as 29.1, 27.7 and 30.4%, respectively. 20,22,24 In comparison with other studies conducted outside Nigeria, the present study reported a higher seroprevalence than those of Iran at 29.0%,Southern Ethiopia 23.9% and Egypt 20.4%.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations